The Representation of Gender Neutrality in Indonesian Physics Textbooks: A Critical Discourse Analysis - Gumilar, Surya; Amalia, Irma Fitria (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2020)
Gender issues in Indonesia are pivotal issues in science/physics textbooks and any aspects of life. As learning resources commonly utilized in the science classroom, physics textbooks should present gender neutrality to urge women's contribution to science. They are frequently considered less performance than those men in science. However, in the Indonesian context, few studies of gender representation in the physics textbook are conducted. Therefore, this present study investigates gender stereotypes in Indonesian physics textbooks based on social actor criteria. A Critical Discourse Analysis (CDA) is a qualitative research method employed to analyze gender neutrality discourse. The use of visual artifacts that refer to the representation of both men and women in the textbooks were utilized to emerge the roles of men and women in three frameworks: laboratory activities, physics application in daily life, and roles of men and women in the family. This present study's findings revealed that representation both men and women were almost to have the same representations based on three of these frameworks. Finally, this present study's implication is to underpin the woman representation to contribute to science activities.